NUMERATION ABILITY OF GRADE IV STUDENTS OF STATE ELEMENTARY SCHOOL 18 PANGKALAN PISANG, SIAK REGENCY - Nova Frianty; Siti Quratul Ain (SOSIOEDUKASI, 2025)
Study This aim analyze in a way comprehensive ability numeracy student Grade IV of SD Negeri 18 Pangkalan Pisang. Research method use approach data triangulation through observation learning , interviews deep with teachers and students , as well as analysis mark test ability numeracy . Findings study indicates existence challenge significant in mastery draft numeracy , in particular related distribution stacked , and implications to ability student in interpret and apply results numeracy in context life daily . Observation results show domination method conventional in learning mathematics , the lack of interaction active students , as well as optimization facility supporters who have not maximum . Interview with the teacher revealing that around 60% of students Still not enough understand draft distribution stacked , difficulty in interpreting the results data division , and constraints Power remember . This is consistent with interview students , where students category low ( for example , Alfarizi Febrian ) admitted Not yet understand distribution stacked and difficult interpret question story , meanwhile student category currently (Gladis Susanti) still Confused with number many and questions story long . Students category height ( Miwan Samsurizal ) shows understanding Good However sometimes Still difficulty with question story complex . Recapitulation mark test confirm that majority students (56.25%) obtained value below 70. Research novelty This lies in the use in-depth data triangulation , providing validity and description holistic about complexity problem numeracy students . Implications study This emphasize urgency further improvement of learning strategies interactive and contextual For increase ability numeracy student in a way comprehensive